Methodological Flaws in Recent Studies of Historical and Modern Witchcraft - Frew, Donald (Ethnologies, 1998)
Academic work of Witchcraft in the last decade has been plagued by fundamental methodological flaws. There has been doctoring of source texts (either through sloppiness or deliberate deception), misrepresentation of sources to bolster counter-arguments, reliance on secondary sources to the exclusion of primary, reliance on unreliable sources when reliable ones are readily available, reliance on "common knowledge” without checking basic facts, reliance on unrepresentative sources when more representative sources are easy to come by, and neglect of alternative hypotheses when such hypotheses are unpopular. The over-all impression is one of a dismissive attitude towards a fringe subject resulting in slip-shod research and analysis. This article examines recent work in the field and exposes many of these basic flaws in methodology, in an effort to assist folklorists responding to Simpson's call to re-evaluate the current work in the field with more critical eyes than have their predecessors and so avoid the same methodological pitfalls.